2021
DOI: 10.1016/j.amepre.2021.01.034
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Governor Political Affiliation and COVID-19 Cases, Deaths, and Testing in the U.S.

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
75
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(87 citation statements)
references
References 20 publications
9
75
0
3
Order By: Relevance
“…In a study of cell phone mobility, Democratic counties were found to be more adherent to governors’ Twitter calls for social distancing compared to Republican counties—regardless of the political affiliation of the governor [ 11 ]. During the second half of 2020 (covering the time period this paper’s research was conducted), preliminary data suggests that the political affiliation of a state’s governor may impact COVID-19 cases and death rates, with Republican-led states harder hit than states led by Democrats [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a study of cell phone mobility, Democratic counties were found to be more adherent to governors’ Twitter calls for social distancing compared to Republican counties—regardless of the political affiliation of the governor [ 11 ]. During the second half of 2020 (covering the time period this paper’s research was conducted), preliminary data suggests that the political affiliation of a state’s governor may impact COVID-19 cases and death rates, with Republican-led states harder hit than states led by Democrats [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this sense this research constitutes additional evidence, complementary to Neelon et al (2), about the importance of ideology and partisanship in the way the US faced and managed the Covid-19 outbreak. Declining pollutant levels also have other major effects on people's health.…”
Section: Introductionmentioning
confidence: 52%
“…The impact of Covid-19 has been anything but random, however, affecting different social groups differently (1). In the United States, political ideology has clashed with the fight against the pandemic (2). During the outbreak of the pandemic, President Donald Trump's denial prevailed over the WHO warnings and scientists who warned of the seriousness of the situation (3).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, we adjusted for potential confounding factors in each county, including healthcare and testing rates (Wu et al, 2020), pre-existing chronic diseases (Townsend et al, 2020), and socioeconomic and demographic (Abedi et al, 2020;Clouston et al, 2021;Karaye & Horney, 2020), political (Neelon et al, 2021), behavioral (Badr et al, 2020;McGrail et al, 2020), and environmental (Chakrabarty et al, 2021; factors.…”
Section: Confounding Factorsmentioning
confidence: 99%